An Ethics of Care in the Teaching of Urban Collective Housing Projects - Patricia Reus; Jaume Blancafort (Dearq)
The main objective of this research was to demonstrate that it is both possible and has value to apply the findings of gendered research on collective housing to the teaching of architectural projects. The methodology developed for this purpose began with experiential learning dynamics aimed at raising students' awareness of spatial imbalances regarding care. This was followed by a creative process supported by criteria selected from the scientific literature and systematized by the teaching staff. An analysis of projects, academic outcomes, and student feedback contributed to the experience and enabled opportunities for improvement to be identified.